Cardiovascular autonomic neuropathy is associated with increased glycemic variability driven by hyperglycemia rather than hypoglycemia in patients with diabetes - Hoda Gad (6470522) (2023)
Aim Cardiac autonomic neuropathy (CAN) has been suggested to be associated with hypoglycemia and impaired hypoglycemia unawareness. We have assessed the relationship between CAN and extensive measures of glucose variability (GV) in patients with type 1 and type 2 diabetes. Methods Participants with diabetes underwent continuous glucose monitoring (CGM) to obtain measures of GV and the extent of hyperglycemia and hypoglycemia and cardiovascular autonomic reflex testing. Results Of the 40 participants (20 T1DM and 20 T2DM) (aged 40.70 ± 13.73 years, diabetes duration 14.43 ± 7.35 years, HbA1c 8.85 ± 1.70%), 23 (57.5%) had CAN. Despite a lower coefficient of variation (CV) (31.26 ± 11.87 vs. 40.33 ± 11.03, P = 0.018), they had a higher CONGA (8.42 ± 2.58 vs. 6.68 ± 1.88, P = 0.024) with a lower median LBGI (1.60 (range: 0.20–3.50) vs. 4.90 (range: 3.20–7.40), P = 0.010) and percentage median time spent in hypoglycemia (4 (range:4–13) vs. 1 (range:0–5), P = 0.008), compared to those without CAN. The percentage GRADEEuglycemia (3.30 ± 2.78 vs. 5.69 ± 3.09, P = 0.017) and GRADEHypoglycemia (0.3 (range: 0 – 3.80) vs. 1.8 (range: 0.9–6.5), P = 0.036) were significantly lower, while the percentage median GRADEHyperglycemia (95.45 (range:93–98) vs. 91.6 (82.8–95.1), P = 0.013) was significantly higher in participants with CAN compared to those without CAN. Conclusion CAN was associated with increased glycemic variability with less time in euglycemia attributed to a greater time in hyperglycemia but not hypoglycemia. Other Information Published in: Diabetes Research and Clinical Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.diabres.2023.110670 Additional institutions affiliated with: National Diabetes Center - HMC